2020
DOI: 10.1101/2020.07.31.230508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural repetition suppression modulates time perception: Evidence from electrophysiology and pupillometry

Abstract: Human time perception is malleable and subject to many biases. For example, it has repeatedly been shown that stimuli that are physically intense or that are unexpected seem to last longer. Two competing hypotheses have been proposed to account for such biases: one states that these temporal illusions are the result of increased levels of arousal which speeds up neural clock dynamics, whereas the alternative ‘magnitude coding’ account states that the magnitude of sensory responses causally modulates perceived … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 137 publications
(215 reference statements)
5
11
0
Order By: Relevance
“…The results indicate that for the first three of those dimensions, changes between the start-and end-marker of an interval resulted in a dilation of perceived duration compared to trials where the start-and end-marker were the same. These findings show that the 'change bias' that we found in earlier work (Kruijne et al, 2020) is a general finding that is not limited to changes in location. At the same time, the results suggest that the change bias shows selectivity, as changes in Faces, Orientation and Luminance did not affect time perception in the same way.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The results indicate that for the first three of those dimensions, changes between the start-and end-marker of an interval resulted in a dilation of perceived duration compared to trials where the start-and end-marker were the same. These findings show that the 'change bias' that we found in earlier work (Kruijne et al, 2020) is a general finding that is not limited to changes in location. At the same time, the results suggest that the change bias shows selectivity, as changes in Faces, Orientation and Luminance did not affect time perception in the same way.…”
Section: Discussionsupporting
confidence: 78%
“…In an earlier study we have demonstrated that the change bias manifests when stimuli marking the start and end of an interval either repeat or change in location (Kruijne et al, 2020). The results suggested that sensory responses to the offset marker were attenuated upon repetition compared to changes, which in turn affected the perceived duration.…”
Section: Experiments 1 : Location and Face Identitymentioning
confidence: 90%
See 3 more Smart Citations